Preparation and characterization of cellulose nanocrystals (CNCs) from pennisetum purpureum (PP) fibers via ammonium persulfate oxidation method - Muhammad Faizullah Pasha; Andoko Andoko; Muhammad Wahid Darmawan; Fina Nur Nabillah; Riduwan Prasetya; Mohammad Sukri Bin Mustapa (Mechanical Engineering for Society and Industry, 2025)
The growing demand for sustainable and high-performance materials emphasizes the need for more efficient production methods for cellulose nanocrystals (CNCs). Traditional CNC synthesis, however, often requires significant energy input and produces harmful by-products, which undermine its environmental and economic viability. In response to this challenge, this study explores the use of an eco-friendly ammonium persulfate (APS) oxidation method to produce CNCs from Pennisetum purpureum fibers. The findings reveal that CNCs synthesized at a temperature of 60 °C exhibited the highest crystallinity index (72.62%), optimal surface functionalization, and exceptional mechanical properties, including a tensile strength of 18.44 MPa.The structural, chemical, and mechanical properties of the CNCs were comprehensively evaluated using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDX), and tensile strength testing. These results highlight the effectiveness of APS oxidation in producing high-quality CNCs from readily available agricultural biomass. By utilizing a sustainable approach, this research not only advances the production of eco-friendly materials but also demonstrates the potential for agricultural waste to be repurposed in nanotechnology applications. The study thus makes a significant contribution to sustainable material science, providing insights into improving CNCs production while minimizing environmental impact, ultimately supporting the transition towards a more sustainable and circular economy.